Atlas Engineering Consultant (AEC) management with android application / Mohammad Zikri Ahmad Sharif - Ahmad Sharif, Mohammad Zikri (2013)
Atlas Engineering Consultant (AEC) is an engineering company that provides building consultancy services business for customer. Currently that company is using manual system using Microsoft Office Excel to write down the proposal project information. To handle AEC using system manually is hard and not efficient. This project develops mobile application for customer request proposal by using mobile phone view at anywhere. That development will use PhoneGap and Java Eclipse programming language. AEC Management with android application is mobile phone application base on android environment that will develop as client application. That application also work as hybrid application category which means combination of native and web-based application that work on client and server side. That application will make user more easily to interact by using mobile phone application. That application able user to register for new user to enter the application. That mobile phone application able to propose project into database server to approve by staff.